All math revision

Description

GCSE Math Flashcards on All math revision, created by katiehumphrey on 16/01/2014.
katiehumphrey
Flashcards by katiehumphrey, updated more than 1 year ago
katiehumphrey
Created by katiehumphrey about 10 years ago
444
27

Resource summary

Question Answer
direct proportion If two quantities are in direct proportion, as one increases, the other increases by the same percentage. If y is directly proportional to x, this can be written as y ∝ x If y is directly proportional to x. When x = 12 then y = 3 Find the constant of proportionality and the value of x when y = 8. We know that y is proportional to x so y = kx We also know that when x = 12 then y = 3 To find the value of k substitute the values y = 3 and x = 12 into y = kx 3 = k × 12 So k = 3/12 = 1/4 To find the value of x , when y = 8 substitute y = 8 and k = 1/4 into y = kx 8 = (1/4) x So x = 32 when y = 8
indirect proportion Inverse proportion is when one value increases as the other value decreases. y is inversely proportional to x. When y = 3, x = 12 . Find the constant of proportionality, and the value of x when y = 8. y ∝ 1/x y = k/x So xy = k Substitute the values x = 12 and y = 3 into xy = k 3 × 12 = 36 So k = 36 To find the value of x when y = 8, substitute k = 36 and y = 8 into xy = k 8x = 36 So x = 4.5
Straight line y ∝ x y = kx This equation gives us a straight line. The gradient of the line is k.
Quadratic y ∝ x2 y = kx2 This equation gives us a curve. The larger the value of k, the steeper the graph.
Cubic y ∝ x3 y = kx3
Square root y ∝square root of x y = ksquare root of x You have similar shaped curves for any powers between 0 and 1. Again, increasing k will make the graph steeper.
Inverse proportion y ∝ 1/x ² y = k/x ² Inverse proportion leads to curved graphs.
surds square root of ab = square root of a x square root of b square root of a x square root of a = a Simplify square root of 12 over square root of 6 Answer square root of 12 over square root of 6 = square root of 12 over 6 (in general square root of a over square root of b = square root of a over b) square root of 2
equations with fractions How do we solve the equation x/2 − 4 = 3? One way is to multiply everything by 2: x/2 − 4 = 3 x - 8 = 6 x = 14 Or, alternatively, add 4 and then multiply both sides by 2: x/2 − 4 = 3 x/2 = 7 x = 14
graph transformations f(x) + a [0/a] f(+ ) = left f(x- ) = right 2f(x) = y coordinates x 2 -f(x) = reflection of f(x) f(2x) = 1/2 x coordinate
sin cos tan graphs
factorising ( x + 2 ) ( x + 5 ) = x2 + 7x + 10 ( x + 2 ) ( x + 3 ) = x2 + 5x + 6 ( x - 3 ) ( x - 5 ) = x 2 - 8x + 15 ( x + 6 ) ( x - 5 ) = x2 + x - 30 ( x - 6 ) ( x + 5 ) = x2 - x - 30
quadratic equations To solve a quadratic equation, the first step is to write it in the form: ax2 + bx + c = 0. Then factorise the equation Solve the equation: x2 - 9x + 20 = 0 Solution First, factorise the quadratic equation x2- 9x + 20 = 0 Find two numbers which add up to 9 and multiply to give 20. These numbers are 4 and 5. (x - 4) (x - 5) = 0 Now find the value x so that when these brackets are multiplied together the answer is 0. This means either (x - 4) = 0 or (x - 5) = 0 So x = 4 or x = 5. You can check these answers by substitutuing 4 and 5 in to the equation: x2- 9x + 20 Substituting 4 gives: 42 - 9 × 4 + 20 = 16 - 36 + 20 = 0 Substituting 5 gives: 52 - 9 × 5 + 20 = 25 - 45 + 20 = 0
completing the square This is another way to solve a quadratic equation if the equation will not factorise. It is often convenient to write an algebraic expression as a square plus another term. The other term is found by dividing the coefficient of x by 2, and squaring it. Rewrite x2 + 6x as a square plus another term. The coeffient of x is 6. Dividing 6 by 2 and squaring it gives 9. x2 + 6x = (x2 + 6x + 9) - 9 = (x + 3)2 - 9
quadratic formula Solve 2x2 - 5x - 6 = 0 Here a = 2, b = -5, c = -6
the quadratic formula
To find the area of the large triangle, you will need to first find the linear/length scale factor as the Step 1. In general to find the scale factor we divide the large quantity with the small quantity. Scale factor = BIG/SMALL =6/4 =1.5 Then Step 2 we would find the Area scale factor by squaring the linear scale factor; ASF = LSF2 =1.52 = 2.25 Step 3 we would multiple the area scale factor with the small area to find the area for the large triangle. Area = 12 x 2.25 = 27cm2
A taxi firm charges £0.50 per mile plus a fixed charge of £2.00. Write down a formula for the cost (C) of hiring this taxi to travel 'n' miles. Solution It costs £2 + £0.50 to travel 1 mile. It costs £2 + 2 x £0.50 to travel 2 miles. It costs £2 + 3 x £0.50 to travel 3 miles. So travelling for 'n' miles will cost £2 + n x £0.50. The formula is C = £2 + (n x £0.50).
Collecting like terms To simplify an expression, we collect like terms. Look at the expression: 4x + 5x -2 - 2x + 7 To simplify: The x terms can be collected together to give 7x. The numbers can be collected together to give 5. So 4x + 5x -2 - 2x + 7 simplified is 7x + 5.
(2x + 5) squared (2x + 5) (2x + 5) = 4x squared + 20x + 25
multiplying out brackets Multiply out: 3(4x - 7) First multiply: 3 × 4x = 12x Then multiply: 3 × -7 = - 21 Therefore: 3(4x - 7) = 12x - 21
multiplying out negatives Multiply out the expression: -3(2n - 8) First, multiply -3 × 2n = - 6n Then multiply -3 × -8 = 24 -6n + 24 Therefore, -3(2n - 8) = - 6n + 24
multiplying out 2 brackets Multiply out these two brackets: (x + 4) (x + 3) Multiply everything in the first bracket by the second bracket: x (x + 3) + 4 (x + 3) = x2 + 3x + 4x + 12 = x2 + 7x + 12
FOIL first outer inner last (n + 4) (n + 4) F n squared O 4n I 4n L 16 n squared + 8n + 16
proof prove (3n + 1) squared - (3n - 1) squared is a multiple of 6 (3n + 1) (3n + 1) = 9n squared + 6n + 1 (3n -1) (3n -1) = 9n squared - 6n + 1 = 12n divided by 6 = 2n its true
Index notation: used to represent powers a2 means a × a and here the index is 2 b3 means b × b × b and here the index is 3 c4 means c × c × c × c and here the index is 4 etc. When there is a number in front of the variable: 4d2 means 4 × d × d 2e3 means 2 × e × e × e
index multiplying and dividing p^3 × p^7 = p^10, and s^5 ÷ s^3 = s^2
solving equations x - 6 + 6 = 9 + 6 x = 15
solving inverse equations Here is how to solve 2a + 3 = 7 using inverses. 2a + 3 = 7 Undo the + 3 by subtracting 3 2a + 3 - 3 = 7 - 3 2a = 4 Then undo the multiply by 2 by dividing by 2 - again on both sides 2a ÷ 2 = 4 ÷ 2 The answer is: a = 2
unknowns on both sides of the equation Solve the equation 3b + 4 = b + 12, and find the value of b. Answer First, you need to get all the b terms on the same side of the equation. Subtract b from both sides. 3b - b + 4 = 12 Then simplify. 2b + 4 = 12 Subtract 4 from both sides. 2b = 8 To find the value of b, divide both sides by 2. b = 4
equations with brackets Solve the equation: 3(b + 2) = 15 3(b + 2) = 15 Multiply out the brackets. Remember, everything inside the brackets gets multiplied by 3. 3 × b + 3 × 2 = 15 When you have multiplied out the brackets you get: 3b + 6 = 15 Next, undo the + 6. In other words, do the inverse and subtract 6 from both sides. 3b + 6 - 6 = 15 - 6 So 3b = 9
trial and improvement Find the answer to the equation x3 – 2x = 25 to one decimal place. First we'll try: x = 3 33 - (2 x 3) 3 x 3 x 3 - (2 x 3) 27 - 6 = 21; too small even if the answer is to 1 decimal place, trial an answer with more than 1 decimal place
simultaneous equations Solve these simultaneous equations and find the values of x and y. Equation 1: 2x + y = 7 Equation 2: 3x - y = 8 Add the two equations to eliminate the ys: 2x + y = 7 3x - y = 8 ------------ 5x = 15 x = 3 Now you can put x = 3 in either of the equations. Substitute x = 3 into the equation 2x + y = 7: 6 + y = 7 y = 1 So the answers are x = 3 and y = 1
solving inequalities Solve the expression 3x - 7 < 8 3x - 7 < 8 Then add 7 to both sides, to cancel out the -7: 3x < 15 Next, simplify the inequality by dividing both sides by the number in front of x - in this case 3. x < 5
double inequalities Solve the inequality -4 < 2x - 6 < 12 Add 6 to all parts: 2 < 2x < 18 Divide all parts by 2: 1 < x < 9
equations for a straight line graph can contain an x term, a y term, and a number
tables for graph plotting
On a graph, parallel lines have the same gradient. For example, y = 2x + 3 and y = 2x - 4 are parallel because they both have a gradient of 2.
the lines y = 2x + 3 and y = -1/2 x -1 cross at right angles
y = mx + c m = gradient c = y intercept
cubic graphs y = x^3
Calculate the points and then plot the graph for the equation y = x3 - x + 8
reciprocal graphs Graphs of the form y = 1/x, 2/x, 3/x
quadratic sequences If the difference between the terms changes, this is called a quadratic sequence. If you use the formula n^2 + n to make a sequence, it means that: When n = 1 you get 1^2 + 1 = 2 When n = 2 you get 2^2 + 2 = 6 When n = 3 you get 3^2 + 3 = 12 When n = 4 you get 4^2 + 4 = 20 - giving the sequence 2, 6, 12, 20.
histograms frequency density = frequency / class width
frequency tables finding the mean and median mean = add all (midpoint x frequency) then divide by total frequency median = total frequency + 1 divided by 2
frequency polygons dot in midpoint
median upper quartile lower quartile and interquartile range of frequency median = frequency + 1 divided by 2 lower quartile = half median upper quartile = median + LQ interquartile range = UQ - LQ
stem and leaf diagram
box plots
The probability of three heads is: P (H H H) = 1/2 × 1/2 × 1/2 = 1/8 P (2 Heads and a Tail) = P (H H T) + P (H T H) + P (T H H) = 1/2 × 1/2 × 1/2 + 1/2 × 1/2 × 1/2 + 1/2 × 1/2 × 1/2 = 1/8 + 1/8 + 1/8 = 3/8
Amit is 12 years old. His brother, Arun, is 9. Their grandfather gives them £140, which is to be divided between them in the ratio of their ages. How much does each of them get? The ratio of their ages is 12:9. We can simplify this. Dividing by 3 gives 4:3. So Amit gets 4 parts, and Arun gets 3. This means that the money has to be divided into 7 parts (4 + 3). £140 ÷ 7 = £20, so 1 part is £20. Amit gets 4 parts: 4 × £20 = £80. Arun gets 3 parts: 3 × £20 = £60.
standard form 15 000 000 = 1.5 × 10 000 000 This can be rewritten as: 1.5 × 10 × 10 × 10 × 10 × 10 × 10 × 10 = 1. 5 × 10^7
adding and subtracting standard form 4.5 × 10^4 + 6.45 × 10^5 = 45,000 + 645,000 = 690,000 = 6.9 × 10^5
multiplying and dividing standard form To multiply powers you add, eg, 10^5 × 10^3 = 10^8 To divide powers you subtract, eg, 10^5 ÷ 10^3 = 10^2
parts of a circle
circumference of a circle pi x diameter
area of a circle pi x (radius squared)
area of a semi circle pi x (radius squared) divided by 2
perimeter of a semi circle (pi x radius) + (2 x radius)
circle theorems
angle at the centre of a circle
angles in the same segment are equal
angles in a semi circle are 90 degrees The angle at the centre (AOB) is twice the angle at the circumference (APB). As AOB is 180°, it follows that APB is 90°
Opposite angles in a cyclic quadrilateral add up to 180° A cyclic quadrilateral is a quadrilateral whose vertices all touch the circumference of a circle. The opposite angles add up to 180o. In the cyclic quadrilateral below, angles A + C = 180o, and angles B + D = 180o
The angle between the tangent and radius is 90° A tangent to a circle is a line which just touches the circle.
difficult circle theorem
quadrilateral has been divided into two triangles, so the interior angles add up to 2 × 180 = 360°. pentagon has been divided into three triangles, so the interior angles add up to 3 × 180 = 540°
interior angles of polygons Interior angle of a regular polygon = sum of interior angles ÷ number of sides
The volume of a pyramid is: 1/3 × base area × perpendicular height The surface area of a pyramid is the area of the base + the area of all the other sides.
The volume of a cone is: 1/3πr^2h The curved surface area of a cone is: πrL (where L is the slant height). Note this doesn't include the area of the base, which is a circle, area πr^2.
The volume of a sphere is 4/3πr^3 The surface area of a sphere is: 4πr^2
volume and area length × length = area length × area = volume area ÷ length = length volume ÷ area = length volume ÷ length = area
3 figure bearings
Pythagoras a^2 + b^2 = c^2
find length of AF AC^2 = 6^2 + 2^2 AC = √40 AF^2 = AC^2 + CF^2 AF^2 = 40 + 3^2 AF = √49 AF = 7cm
We are given angle A and side AB. AB is the hypotenuse. BC is opposite angle A. Therefore we use the formula: sin = opposite / hypotenuse sin 30 = BC / 7 Multiply both sides by 7 7 x sin30 = BC Using a calculator we get BC = 3.5cm
The answer is 4.77cm (3 sf). Can you see that PQ is opposite the given angle and that QR is adjacent to it? Use the formula: tan = opposite / adjacent tan50 = PQ / 4 4 × tan50 = PQ PQ = 4.77 (3 sf)
We are given angle Z XZ is adjacent to angle Z. YZ is the hypotenuse. Therefore we use the formula: cos = adjacent / hypotenuse cos 25 = 5 over YZ This time our unknown side (YZ) is the denominator. If we multiply both sides by YZ, we get: YZ x cos 25 = 5 over YZ x YZ YZ x cos25 = 5 Now we can divide both sides by cos25: YZ x cos 25 over cos 25 = 5 over 25 YZ = 5 over cos 25 Using a calculator: YZ = 5 ÷ 0.9063 = 5.52cm (3 sf)
AC is adjacent to angle C. BC is the hypotenuse. So we use the formula: cos = adjacent / hypotenuse cosC = 5/7 To calculate C we need to find the inverse of cos (INV cos or SHIFT cos): C = Inv cos(5/7) Using a calculator: C = 44.4°
the sine rule
R = 25.4° Using the sine we can write: sinR over 4 = sin75 over 9 Multiplying both sides by 4, we get sinR = sin75 over 9 x 4 = 0.4293... SO R = inv sin(0.4293) R = 25.4° (1dp)
the cosine rule
a^2 = b^2 + c^2 - 2bc cos A Substitute the values into the formula. a^2 = 7^2 + 3^2 - 2 × 3 × 7 cos 35 a^2 = 58 - 42 cos 35 a^2 = 23.5956 a = 4.86cm
area of a triangle ABC = 1/2 ab sin C
Area = 12.4cm^2 The area of the triangle is 1/2 × 5.2 × 7.1 x sin42 = 12.4cm^2
Show full summary Hide full summary

Similar

Pythagorean Theorem Quiz
Selam H
Geometry Vocabulary
patticlj
Algebra 2 Quality Core
Niat Habtemariam
GRE Study Precalc
Marissa Miller
Geometry Formulas
Selam H
MODE, MEDIAN, MEAN, AND RANGE
Elliot O'Leary
CUMULATIVE FREQUENCY DIAGRAMS
Elliot O'Leary
Statistics Equations & Graphs
Andrea Leyden
Using GoConqr to teach Maths
Sarah Egan
Using GoConqr to study Maths
Sarah Egan
STEM AND LEAF DIAGRAMS
Elliot O'Leary